Content management in a mobile ad hoc network: beyond opportunistic strategy. (1st January 2013) - Lee, Suk-Bok; Wong, Starsky Ho Yin; Lee, Kang-Won; Lu, Songwu
We study the challenging problem of strategic content placement in a dynamic MANET. Existing content placement techniques cannot cope with such network dynamics since they are designed for fixed networks. Opportunistic caching approaches are insufficient as they do not actively manage contents for certain goals. In this paper, we present a novel content management approach, called LACMA that leverages the location information available to mobile devices via GPS. The main insight behind LACMA is to bind data to geographic location (as opposed to network nodes). This location-based strategy decouples the content placement problem from the changing network topology, and allows us to design an optimisation framework even in a dynamic MANET environment. We present key components of LACMA used for strategic content placement and content-location binding (through proactive content push). We evaluate LACMA and compare its performance with existing caching schemes and show that LACMA considerably outperforms existing schemes over a wide range of scenarios.